MORPHOLOGICAL SIGNS DEVELOPING IN THE STOMACH OF WHITE-BREEDLESS RATS IN EXPERIMENTAL PULMONARY FIBROSIS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Among the countries of the world, the deterioration of the ecological situation, the increase of various risk factors have a negative effect on the human body. As a result of the development of pathological processes, a number of morphometric and morphological changes occurred in the anatomical structure and mucous membranes of the stomach. The medical and social importance of digestive diseases is determined by their prevalence, as well as the annual increase in morbidity and mortality.